Studi Lama dan Jenis Kontrasepsi Hormonal yang Digunakan dengan Gangguan Menstruasi Akseptor KB Aktif di Wilayah Kerja Puskesmas Jati Raya Kota Kendari - Amiruddin, Amiruddin; Agriansyah A, Agriansyah A; Risna, Risna (Fakultas MIPA UNM, 2019)
Abstract. Based on initial observations on hormonal contraceptive KB acceptors in the working area of the Jati Raya Health Center in Kendari City, many acceptors experience menstrual disorders. This study aims to determine the relationship between duration of use and the type of hormonal contraception used with menstrual disorders inactive family planning acceptors in the working area of Jati Raya Health Center, Kendari City. This type of research is an association with the Cross-Sectional Study design. The population in this study was 153 acceptors. The sample was determined by purposive sampling of 138 respondents using a questionnaire. The results showed respondents with a duration of use <6 months (45.7%), 6 months - 1 year (31.2%), and> 1 year (23.2%), the type of hormonal contraception used is; injections (80.4%), pills (13.8%) and implants (5.8%), menstrual disorders before using hormonal contraceptives namely; normal (39.1%) and mild disorders (60.9%) and after using hormonal contraception, mild disorders (15.9%), moderate (39.1%) and severe (44.9%). The results of data analysis with the chi-square test concluded that the length of hormonal contraceptive use was significantly related to menstrual disorders in active KB acceptors in the working area of the Jati Raya Health Center in Kendari City and the type of hormonal contraception used was significantly related to menstrual disorders in active KB acceptors in the Puskesmas work area. Jati Raya Kendari City (p <0.05). Keywords: old, hormonal contraception, menstrual disorders, family planning acceptors.